Effects of reduction and polystyrene sulfate functionalization on the capacitive behaviour of thermally exfoliated graphene - Yan, Yinan; Kuila, Tapas; Kim, Nam Hoon; Ku, Bon-Cheol; Lee, Joong Hee (ROYAL SOC CHEMISTRY, 2013)
Thermally exfoliated and reduced graphite oxide (TEG) was prepared at high temperature (1000 degrees C). The supercapacitor behavior of the resulting TEG would be affected by the specific surface area (SSA) and the surface interactions of the remaining oxygen functional groups with the electrolyte media. The oxygen functional groups on the surface of TEG were controlled by varying the duration of thermal treatment (5, 10, 20, 30 and 45 s). Polystyrene sodium sulfate (PSS) functionalized TEG (PSS-f-TEG) was prepared to aid the interaction with the polar groups of the electrolyte media and its electrochemical performance was measured. Fourier transform infrared and X-ray photoelectron spectroscopy were used for the qualitative and quantitative detection of residual oxygen functionalities in the pristine graphite oxide and resulting TEGs. It was found that the residual oxygen functionalities in the TEGs decreased with increasing thermal treatment time and the SSA increased initially. A maximum SSA of 400.7 m(2) g(-1) was obtained for 30 s thermally treated TEG. The highest specific capacitance value of 278.8 F g(-1) was observed for PSS-f-TEG (with 10 s treatment). It was found that the wettability of the TEG was increased after surface modification with PSS as evident from the contact angle analysis. The oxygen functionalities of graphene directly enhanced the specific capacitance by contributing pseudocapacitance. The 1000 charge-discharge cycle test showed long-term electrochemical stability of the electrode materials with 97% retention in specific capacitance.
Keywords: SUPERCAPACITOR ELECTRODES; CARBON NANOTUBES; GRAPHITE OXIDE; NANOSHEETS; FILMS; COMPOSITES; HYBRID; SHEETS; MNO2